Implementing Project-Based Learning to Enhance Students’ Creativity in Indonesian Language Learning at Elementary School - Hamdi, Zulfadli; Sururuddin, Muhammad; Yunida, Liza (Papanda Publisher, 2025)
This study aimed to analyze the effect of the project-based learning (PjBL) model on students’ creativity in Indonesian language learning in Grade V at SDN 1 Montong Baan. The study was motivated by the low level of students’ creativity due to conventional teacher-centered learning and limited opportunities to explore ideas. A quantitative approach with a one-group pretest–posttest experimental design was employed. The sample consisted of 20 students selected using a saturated sampling technique. A validated and reliable creativity questionnaire was used as the research instrument. Data were analyzed using normality and paired t-tests to compare pre- and post-intervention scores. The findings revealed a significant increase in students’ creativity scores, from a pretest mean of 42.45 to a posttest mean of 77.15. The hypothesis test showed that the t-value (174.25) exceeded the t-table value (1.725) at the 0.05 significance level. These results confirm that implementing PjBL effectively enhances students’ creativity. The discussion highlights that the real-life project characteristics of PjBL encourage students to be more active, collaborative, and confident in expressing creative ideas. This study recommends applying PjBL as an alternative instructional strategy in elementary Indonesian language learning to foster students’ creativity.